Pengaruh peredaran uang kartal, uang elektronik, kurs, suku bunga SBI dan harga bahan bakar minyak terhadap inflasi di Indonesia - Yudi, Yudi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to analyze the effect of circulation of currency, electronic money, exchange rates, SBI interest rates and fuel oil prices on inflation in Indonesia. This research is motivated by the development of electronic money and the decreasing of currency in the community so that it plays a role in increasing inflation. The method in this study is through a quantitative approach. This research uses multiple linear regression with Ordinary Least Square method of Eviews-12 program. The results of this study prove that simultaneously the circulation of currency, electronic money, exchange rates, SBI interest rates and fuel oil prices have a significant effect on inflation. But partially, electronic money, SBI interest rates and fuel oil prices have a significant effect on inflation. While the circulation of currency and exchange rate has no significant effect on inflation. By looking at the results of this study, it is expected to be useful, especially for monetary authorities in formulating appropriate policies related to currency, electronic money, exchange rates and SBI interest rates to control inflation. Likewise, it is expected to be useful for the Government in managing fuel oil prices that can control inflation in Indonesia.